(untitled) (Homoeopathy for All, 2023)
Renal cysts, also known as kidney cysts, are fluid-filled sacs that develop in the kidneys. They have a thin wall and can range in size from a small pea to as large as a grapefruit. Renal cysts are usually round or oval in shape and become fairly common as people age. A simple kidney cyst is the mostcommon type of renal cyst. One or more simple cysts may form within the same kidney. They are usually asymptomatic and do not damage the kidneys or affect their function. Simple renal cysts are detected incidentally upon radiological exams of the abdomen. They are usually non-cancerous and rarely require treatment unless they grow significantly in size, become infected, or cause discomfort.